Ensayo y validacion de tecnologia en el cultivo de la yuca - International Center for Tropical Agriculture (International Center for Tropical Agriculture, 1979)
This expt, that is currently being carried on in Mondomo (Cauca, Colombia) seeks to validate the technology produced by the CIAT Cassava Program, with promising var. and adequate agricultural practices; and to evaluate and compare traditional vs. new technology under farming conditions. A technological package is expected to be obtained on the basis of this evaluation, and after measuring the economic impact produced by this new technology and determining important marketing aspects; this will be implanted by the national agricultural research program and diffused in the area by their technicians. In this 1st stage, a socioeconomic survey was applied to 20 farmers selected at random, 7 of whom (also chosen at random) were willing to prepare 4000 m2 to plant 3 CIAT cv. (CM 323-375, M Col 1684 and CMC 59) in addition to 2 regional var., Algodona and Americana. The 6 proposed treatments are discussed. (CIAT)